Optimizing nutrition in older people. (June 2018) - Clegg, Miriam E.; Williams, Elizabeth A.
Highlights: Older adults are at increased risk of malnutrition due to both physiological and psychological causes. Simple strategies to increase food intake include increasing variety, and enhancing the palatability or flavour of foods. Protein is vital for muscle mass maintenance and may be effectively delivered to older adults via protein enriched drinks. Providing opportunities for older adults to eat with others or to prepare meals is well established to enhance food intake. Other aspects that need to be considered are safe food preparation and food packaging. Abstract: Older adults are at increased risk of malnutrition, for a variety of physiological and psychological reasons. This has implications for health, quality of life, independence and economic circumstances. Improvements in nutrition are known to bring tangible benefits to older people and many age-related diseases and conditions can be prevented, modulated or ameliorated by good nutrition. However, practical and realistic approaches are required to optimize diet and food intake in older adults. One area where improvements can be made relates to appetite. Encouraging older adults to prepare meals can increase appetite and food intake, and providing opportunities for older adults to eat a wide variety of foods, in company, is a simple strategy to increase food intake. The protein requirement of older adults is subject to controversy and although considered the most satiating macronutrient, it appears that protein does not elicit as great a satiating effect in older adults as it does in younger individuals. This indicates that there is potential to increase protein intake without impacting on overall energy intake. Other areas where simple practical improvements can be made include both packaging of foods that are easy to prepare and the education of older adults on the safe storage and preparation of food. Research into improving the diets and nutritional status of older adults has indicated that many of the strategies can be easily and cost-effectively undertaken.